2020
DOI: 10.1101/2020.08.11.20173005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histopathology of Third Trimester Placenta from SARS-CoV-2-Positive Women

Abstract: Background: This study aims to investigate whether maternal SARS-CoV-2 status affect placental pathology. Methods: A retrospective case-control study was conducted by reviewing charts and slides of placentas between April 1 to July 24, 2020. Clinical history of COVID-19 were searched in Pathology Database (CoPath). Controls were matched with SARS-CoV-2-negative women with singleton deliveries in the 3rd-trimester. Individual and group, pathological features were extracted from placental pathology reports. Re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 19 publications
0
15
0
2
Order By: Relevance
“…We identified a total of 1452 cases from 30 publications [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ] ( Table 1 ). It should be taken into consideration that histological changes were not graded in all publications and even minor changes could have been summarized as “pathology”.…”
Section: Resultsmentioning
confidence: 99%
“…We identified a total of 1452 cases from 30 publications [ [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ] ( Table 1 ). It should be taken into consideration that histological changes were not graded in all publications and even minor changes could have been summarized as “pathology”.…”
Section: Resultsmentioning
confidence: 99%
“…Results of early studies examining the effects of maternal SARS-CoV-2 infection on the placenta suggested an association between maternal SARS-CoV-2 infection and maternal or fetal vascular malperfusion [8][9][10][11][12][13][14][15] however later studies failed to support these conclusions [13][14][15][16][17] These early studies were largely retrospective reviews of placentas from all SARS-CoV-2 infected mothers, irrespective of active placental infection (i.e., no confirmation of SARS-CoV-2 infection in the placental parenchyma). More recently, case reports with confirmatory testing for active placental infection have highlighted recurring features of chronic histiocytic intervillositis, 4,[18][19][20][21][22][23][24][25] villous trophoblast necrosis, 4,18,[23][24][25][26] and, to varying extents, intervillous fibrin deposition.…”
Section: Introductionmentioning
confidence: 99%
“…15 Furthermore, there are indications from several case reports that SARS-CoV-2 infection during pregnancy is associated with placental pathological changes, including placentitis, intervillositis, fibrin deposition, and decidual vascular injury. 14,[16][17][18][19] Moreover, placental infection was reported with the presence of the viral RNA in the umbilical cord, the placental villi, fetal membranes, and trophoblasts, raising concerns that SARS-CoV-2 could affect fetal development. 20,21 Severe neonatal COVID-19 is described and sporadic cases of vertical transmission were reported.…”
Section: Introductionmentioning
confidence: 99%